PENGEMBANGAN BAHAN AJAR STATISTIKA BERBASIS INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) - Suryani Lukman, Hamidah; Sutisnawati, Astri (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2016)
This paper is the research and development result of Statistics teaching materials based on ICT. The method used is the early stage of research and development that applied on the second phase of the study. The first stage is analysis the teaching materials through the study of literature; developing initial products; experts team validation;  and  first  revised.  The  second phase is limited test to 13 students randomly selected that participated in the course Statistics on Mathematics Education Universitas  Muhammadiyah  Sukabumi,  and do the second revised. The method used in the second stage is a single experiment one shot case study. The instrument used in this study are validation sheet, teaching materials performance and effectiveness sheet, and conceptual understanding test. These data were analyzed using descriptive analysis and Wilcoxon Signed Ranks Test on the level of ? = 5%. The results showed that average score of teaching materials validation is 4.50 out of This result indicates that more than 80% of ICT based teaching materials developed is feasible to use (valid) and classified as very well   category.   Based   on   trial   results, conceptual understanding ability of students after  using  ICT  based  teaching  materials significantly  better  than  before  using  ICT based teaching materials. In addition, an overall assessment of performance effectiveness of ICT based teaching material reached 62.98% higher than the learning without ICT based teaching materials, which only reached 60.58%. These results indicate that using ICT based teaching materials in learning   has   the   valid,   practical,   and effective criteria, particularly in an effort to develop the students? conceptual understanding ability.